2023
DOI: 10.1021/acsnano.3c00467
|View full text |Cite
|
Sign up to set email alerts
|

Self-Destructive Structural Color Liquids for Time–Temperature Indicating

Abstract: Vaccines are undoubtedly a powerful weapon in our fight against global pandemics, as demonstrated in the recent COVID-19 case, yet they often face significant challenges in reliable cold chain transport. Despite extensive efforts to monitor their time–temperature history, current time–temperature indicators (TTIs) suffer from limited reliability and stability, such as difficulty in avoiding human intervention, inapplicable to subzero temperatures, narrow tracking temperature ranges, or susceptibility to photob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…The calculated volume fraction of dispersions with assembled crystals ranges from ∼1 to ∼5 vol %, based on the density of amorphous and crystalline SiO 2 (Figure d). In contrast, the typical lowest concentration required for SiO 2 nanosphere assembly is ∼30 vol %. ,,, Additionally, it enables the fabrication of photonic crystals with the same color using nanospheres of a much smaller size (84 nm vs 190 nm).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The calculated volume fraction of dispersions with assembled crystals ranges from ∼1 to ∼5 vol %, based on the density of amorphous and crystalline SiO 2 (Figure d). In contrast, the typical lowest concentration required for SiO 2 nanosphere assembly is ∼30 vol %. ,,, Additionally, it enables the fabrication of photonic crystals with the same color using nanospheres of a much smaller size (84 nm vs 190 nm).…”
Section: Resultsmentioning
confidence: 99%
“…Decades of investigation have revealed that the ordered self-assembly of these highly charged nanospheres in solution is driven by minimizing the free energy arising from electrostatic repulsive interactions. , Although there is no clear distinction, the reported systems can be roughly classified by the required volume fraction of the colloidal solution. Some systems only show photonic crystals assembled at high volume fractions (i.e., >30 vol %), ,,,, while others do not require such a high concentration (i.e., ∼1–15 vol %). ,, As the ordering of nanoparticles results from electrostatic repulsion, the required volume fraction reflects the effective range of this interaction, which is determined by the thickness of the electrical double layers (EDL).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the integration of temperature-responsive color changes could potentially enable the realization of an unconstrained environmental monitoring system and locally driven soft robot systems. 68 This advancement would expand the application of soft robotics for biomedical applications.…”
Section: Response Principle Of the Single-layer Hydrogel Robotmentioning
confidence: 99%
“…Khandelwal et al have developed a static infrared reflector that can block IR radiation from the sun without affecting visible transparency. Huang et al have prepared a temperature monitoring material that self-destructs when it reaches its melting point of the solution, causing irreversible fading of the material; however, this material is not reusable and results in material waste. Furthermore, cholesteric phase liquid crystals at room temperature exhibit bistable states and temperature control characteristics.…”
Section: Introductionmentioning
confidence: 99%